Proceedings of the John Hall Symposium : In Honor of John Hall on the Occasion of His 70th Birthday. - Bergquist, James C. (World Scientific Publishing Company, 2006)
This symposium was a dedication to John L Hall, who was recently awarded the Nobel Prize in Physics, (report below). The symposium was a celebration of his striking career in physics and his impressive record of achievements. Papers included in this volume offer brief and personal glimpses of some of his achievements, the research he inspired, and the great friendships he has built. Nobel Prize Report:. John L Hall, a Scientist Emeritus of the National Institute of Standards and Technology and a Fellow of JILA (joint institute of NIST and University of Colorado) has been awarded the 2005 Nobel.